2017
DOI: 10.2337/dc17-0303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Telemedical Lifestyle intervention Program TeLiPro in Advanced Stages of Type 2 Diabetes: A Randomized Controlled Trial

Abstract: OBJECTIVELifestyle interventions are the foundation of treatment in newly diagnosed type 2 diabetes. However, their therapeutic potential in advanced disease stages is unknown. We evaluated the efficacy of the Telemedical Lifestyle intervention Program (TeLiPro) in improving metabolic control in advanced-stage type 2 diabetes. RESEARCH DESIGN AND METHODSIn this single-blind, active comparator, intervention study, patients with type 2 diabetes (with glycated hemoglobin [HbA 1c ] ‡7.5% [58.5 mmol/mol]), and BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 30 publications
5
141
0
13
Order By: Relevance
“…13 In addition, it may be difficult to engage asymptomatic, scarcely motivated patients with NAFLD in intensive lifestyle protocols, because of space and time constraints. 14 eHealth technology is a possible resource to promote behavior changes, 15 thus reducing NAFLD progression. The possibility to educate, to counsel and to induce permanent changes in motivated and engaged patients with NAFLD via an internet-based approach would reduce attendance to busy liver units, sparing patients' and physicians' time, and would expand lifestyle intervention to a much larger community.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, it may be difficult to engage asymptomatic, scarcely motivated patients with NAFLD in intensive lifestyle protocols, because of space and time constraints. 14 eHealth technology is a possible resource to promote behavior changes, 15 thus reducing NAFLD progression. The possibility to educate, to counsel and to induce permanent changes in motivated and engaged patients with NAFLD via an internet-based approach would reduce attendance to busy liver units, sparing patients' and physicians' time, and would expand lifestyle intervention to a much larger community.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many of the current, web‐based self‐management systems for insulin titration require dose‐validation by HCPs. This is the case for the PREDICTIVE 303 algorithm, the LTHome system and TeLiPro . Studies with the Diabetes Pal smartphone and the MyStar DoseCoach glucometer included patients already treated with insulin and failed to show superiority in terms of HbA1c reduction.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for the PREDICTIVE 303 algorithm, 8,9 the LTHome system 10 and TeLiPro. 11 Studies with the Diabetes Pal smartphone 12 showed an additional HbA1c reduction (−0.7%) by using an algorithmic insulin titration guidance (d-Nav device) with HCP support F I G U R E 2 A, Changes from baseline in HbA1c levels at M4 and M13. HbA1c levels decreased more in patients from the G2 and G3 arms compared with the control arm, G1 (−0.53% and −0.51%, respectively; ***P < 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…К таким проектам относится "Teli-Pro" -результат комбинации 5 компонентов: телемониторинга, телемедицинского коучинга, медико-ментальной мотивации, диеты и самоконтроля. Результаты проспективного рандомизированного исследования пациентов с СД2 показали эффективность такой программы не только в отношении гликемического контроля и приверженности лечению, но и всех метаболических показателей [81].…”
Section: терапевтическое обучение и программы поддержки пациентовunclassified